Towards internalising values and attaining performance for globally respected university 2024 / Prof. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
UiTM members (academics, non-academics, students and supporting staff) are globally recognised due to their involvement in their niche areas (professional bodies/ association/ institutions, G2G, media) whereby their ideas are accepted and be part of the global community.